Characterization of IN 625 recycled metal powder used for selective laser melting - Condruz Mihaela Raluca (Manufacturing Review, 2020)
Additive manufacturing of high-quality materials by Selective Laser Melting depends not only on establishing appropriate process parameters, but also on the characteristics of the metal powders used and their stability over time or after recycling. The aim of the research was to characterize the IN 625 powder used over multiple manufacturing cycles with a Lasertec 30 SLM machine. In order to achieve the research's goal, virgin and recirculated powder's physical and technological characteristics were investigated. A decrease in all D-values (D10, D50, D90) of the powder size distribution was observed after multiple recirculation cycles showing a decrease of the powder dimensional range over time. Both virgin and recirculated powders are composed of mainly spherical particles, but elongated particles and satellite particles were observed as well. The dimensional evolution analysis showed a deviation from the powder ideal roundness, deviation that is more pronounced over multiple recirculation cycles. It was experimentally determined that the powders present a good flowability based on the flow rate value obtained for both virgin and recirculated powders, confirmed also by the Hausner ratio and angle of repose.